2004
DOI: 10.1111/j.1572-0241.2004.04039.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Appendectomy are Risk Factors for Extraintestinal Manifestations in Ulcerative Colitis

Abstract: In UC patients, appendectomy and cigarette smoking are prognostic factors for the development of EIM. The unfavorable effect of cigarette smoking on EIM is additive to that of appendectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 53 publications
2
21
1
Order By: Relevance
“…68 Extraintestinal manifestations occur in both UC and CD 69 indicating that systemic immunity is affected in IBD. In UC, extra-intestinal manifestations may be associated with smoking, 70 but the cytokine and cell cycle models were not affected by smoking habit.…”
Section: Discussionmentioning
confidence: 99%
“…68 Extraintestinal manifestations occur in both UC and CD 69 indicating that systemic immunity is affected in IBD. In UC, extra-intestinal manifestations may be associated with smoking, 70 but the cytokine and cell cycle models were not affected by smoking habit.…”
Section: Discussionmentioning
confidence: 99%
“…Present knowledge concerning the impact of smoking on course or incidence of diseases comprises both negative and positive effects. Among the autoimmune diseases, smoking was proven to be associated with an increased risk of Crohn's disease, greater severity of fibromyalgia, and higher risk for extraintestinal manifestations in ulcerative colitis [1][2][3]. Many studies have also focused on the correlation between smoking and rheumatoid arthritis (RA); here, smoking was identified as an important risk factor for the development and severity of RA, particularly in heavy smokers [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that current cigarette smoking in UC patients increased the risk of articular and dermatological EIMs, whereas no such increase was observed in ocular or hepatobiliary complications. 38 Current or previous smoking has also been shown to reduce instances of primary sclerosing cholangitis 1,5,6,24,[39][40][41] and backwash ileitis. 24 The literature remains divided, however, regarding smoking's effect on pouchitis following colectomy with ileal pouch-anal anastomosis.…”
Section: 21mentioning
confidence: 99%